The Use of TikTok for Learning English Vocabulary - Pratiwi Anjar Sari Hasan; Rasuna Talib; Magvirah El Walidayni Kau (English Education Department, 2025)
Learning English vocabulary using TikTok as a media learning is expected to provide students with a practical, engaging, and meaningful learning experience. This research aims to determine the implementation of teaching English vocabulary to fifth-grade students of SD Laboratorium UNG through TikTok media. This study used a qualitative approach with a descriptive case study design, involving 20 fifth-grade students at SD Laboratorium UNG in the academic year 2024/2025 as research subjects. The data were collected through observation, interviews, and documentation, focusing on three basic types of vocabulary: nouns, verbs, and adjectives, which were taught using TikTok videos. This research showed that (1) using TikTok videos in the classroom increases students’ interest, participation, and understanding of English vocabulary. This was proven by observations that have been analyzed about the implementation of TikTok videos as a medium for learning English vocabulary to fifth-grade students at SD Laboratorium UNG. (2) students showed improvement in recognizing, pronouncing, and using vocabulary in simple sentences, and felt more confident in the learning process. This is based on the results of interviews conducted with 5 students who were most active during the implementation of TikTok videos in English vocabulary learning activities. Despite challenges such as limited access to technology, TikTok proved to be an effective medium for teaching vocabulary to young EFL learners. Keywords: TikTok, Vocabulary, Learning Media, Young Learners